Examination of the Myokine Response in Pregnant and Non-pregnant Women Following an Acute Bout of Moderate-Intensity Walking - Hutchinson, Kelly Ann; Mohammad, Shuhiba; Garneau, Léa; McInnis, Kurt; Aguer, Céline; Adamo, Kristi B. (Frontiers in Physiology, 2019)
Background: It is recommended that women accumulate 150 min of weekly moderate-intensity physical activity (MPA) when pregnant. Engaging in regular physical activity (PA) confers many health benefits to both the mother and the fetus. However, the molecular mechanisms by which these health benefits are bestowed are not well understood. One potential factor that may be contributing to the observed benefits is myokines, which are small peptides secreted by skeletal muscles. In the non-pregnant population, myokines are believed to be involved in the molecular mechanisms resulting from PA. The objective of this study was to characterize and compare the myokine profile of pregnant and non-pregnant women, after an acute bout of MPA. Methods: Pregnant (n=13) and non-pregnant (n=17) women were recruited from the Ottawa region to undergo a treadmill walking session at moderate-intensity (40-50% heart rate reserve). Pre- and post-exercise serum samples were taken and a set of 10 myokines were analyzed. IL-6 was analyzed using a high-sensitivity assay, while FGF21, EPO, BDNF, Fractalkine, IL-15, SPARC, FABP-3, FSTL-1, oncostatin were analyzed using various multiplex assays. Results: The pregnant and non-pregnant groups did not differ in terms of age, height, non/pre-pregnancy weight, BMI and resting heart rate. Baseline levels of myokines were compared between both groups showing a higher concentration for EPO, IL-15 and oncostatin in the pregnant group, while FGF-21 was higher in the non-pregnant group. Circulating levels of 5 myokines, FGF21, EPO, BDNF, fractalkine, and IL-15 significantly increased in response to the acute exercise in the pregnant group. Non-pregnant women exhibited an increase in six myokines, BDNF, Fractalkine, SPARC, FABP-3, FSTL-1 and oncostatin, while one myokine, EPO, decreased post-exercise. Conclusion: This is the first study examining myokine response following an acute bout of PA in pregnancy. Moderate intensity PA, which is recommended during pregnancy, elicited an increase in five myokines post-compared to pre-exercise in the pregnant group. Further research is warranted in order to understand the role of myokines in pregnancy.